2009
DOI: 10.1089/aid.2009.0005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of HIV Type 1 along the Coastal Strip of Kenya

Abstract: A study on the genetic diversity of HIV-1 subtypes present along the coastal strip of Kenya, i.e., Kilifi, Mombasa, Msambweni, and Malindi districts, was carried out. DNA sequences for regions encoding a portion of the env-gp41 region of the virus were generated by PCR and sequenced directly. Eighty six samples that were successfully sequenced were analyzed. From the analysis, 86% (74) were subtype A1, 5% (4) were subtype C, 8% (7) were subtype D, and 1% (1) was subtype G. This study shows that HIV-1 subtype A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
16
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 15 publications
2
16
1
Order By: Relevance
“…[8][9][10][11] In two previous studies in Northern Kenya, we reported 50-57% of all HIV-1 in that region as subtype A, followed by subtypes C and D at 27-39% and 9-11%, respectively. 8,10 This pattern appeared to be influenced by cross-border population dynamics as we observed.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…[8][9][10][11] In two previous studies in Northern Kenya, we reported 50-57% of all HIV-1 in that region as subtype A, followed by subtypes C and D at 27-39% and 9-11%, respectively. 8,10 This pattern appeared to be influenced by cross-border population dynamics as we observed.…”
mentioning
confidence: 76%
“…We later reported a different pattern at the Kenyan coast where the prevalence of subtype A1 was much higher at over 85%. 9 These rates may continue to vary as the evolutionary forces of host immunity and antiretroviral pressure exert influence. 5,12,13 Indeed, slow rates of evolution of subtype B in the western setting were found to track with the escalation of antiretroviral treatment (ART), while an increase in evolutionary rates of HIV-1C was associated with declining prevalence among Ethiopians.…”
mentioning
confidence: 99%
“…This is consistent with previous reports on HIV subtypes in Kenya, where subtype A has been shown to be the most common HIV subtype. [20][21][22][23] The second most common viral subtype was D with a prevalence of 22%. This is also consistent with previous studies, where subtype D has been reported to be the second most prevalent subtype in Kenya (www.hiv.lanl.gov/).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Little is known about circulating subtypes of HIV-1 in rural areas, which are the home to many of the infected people. In this study, we sought to determine the circulating subtypes of HIV-1 in eight districts of central Kenya in which HIV-1 prevalence has been known to be high.…”
mentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMCs) were extracted from whole blood by density gradient centrifugation using Ficoll-Paque Plus (Pharmacia) and Proviral DNA extracted using DNAzol (Gibco BRL) and ethanol precipitation as previously described. 12,13 A segment of the env gp41 (corresponding to nucleotide 7850-8310 of HIV-1 HXB2 ) was amplified with primers, gp40F1 5'-TCTTAGGAGCAGCAGGAAGCACTATGGG-3¢ and gp41R1 5'-AACGACAAAGGTGAGTATCCCTGCCTAA-3' in the first round and gp46F2 5'-ACAATTATTGTCTGGTA TAGTGCAACAGCA-3' and gp47R2 5'-TTAAACCTAT CAAGCCTCCTACTATCATTA-3' for nesting. Amplification was done with one cycle of 95°C for 10 min and 35 cycles of 95°C for 30 s, 55°C for 30 s, and 72°C for 1 min, with a final extension of 72°C for 10 min.…”
mentioning
confidence: 99%